PERANCANGAN SISTEM INFORMASI PENGELOLAAN KEUANGAN PADA PT. NAULI TOUR & TRAVEL - Albert Rinaldy Sibarani; Marlyna Infryanty Hutapea; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
PT. Nauli Tour & Travel is a company engaged in the tourist travel section located in Medan, North Sumatra. PT. Nauli Tour & Travel is here to serve customer needs for tourism services. Therefore, PT. Nauli Tour has some data that require computerized data management so that the information generated can be maximized. One of the things that require computerized data management is financial data management, where financial data is one of the most important assets in any company. Computerized management of financial data must also be accompanied by better security so that its security is guaranteed. The process of managing financial data at PT. Nauli Tour & Travel is currently computerized, but financial data management is carried out at Microsoft Exel so that the security of the financial data is still lacking. In this research, the writer will design an information system that can be used by PT. Nauli Tour & Travel in managing financial data so that the information generated is maximized.